Democracy as a Manifestation of Civilizational Mediocrity - the Thought of Nikolai Berdyaev - Jedliński, Marek (Sensus Historiae, 2022)
The purpose of this article is to present Nikolai Berdyaev’s view on democracy. Berdyaev regarded the metaphysics of democratism as a manifestation of human hubris and a fall into what is mediocre and devoid of deeper spirituality. Mediocrity was revealed in civilization. Berdyaev’s critique of democracy was grounded in the conviction that power should be aristocratic, not egalitarian. In his view, only the chosen, few, the eminent, possessed the ability to guide the masses toward the highest values and beauty.